2015
DOI: 10.1186/s13104-015-1525-x
|View full text |Cite
|
Sign up to set email alerts
|

The pla gene, encoding plasminogen activator, is not specific to Yersinia pestis

Abstract: Here we present evidence to show that the pla gene, previously thought to be specific to Yersinia pestis, occurs in some strains of Citrobacter koseri and Escherichia coli. This means that detection of this gene on its own can no longer be taken as evidence of detection of Y. pestis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The results found here supports other work which suggests that markers other than the pla gene should be included to help avoid false positive results when screening for Y. pestis , as has been stressed by Janse, Hamidjaja & Reusken (2013). This was recently confirmed by Hänsch et al, as they found evidence that the pla gene is present in some strains of Escherichia coli and Citrobacter koseri (Hänsch et al, 2015). It is not clear why the homologue was present in a larger percentage of R. rattus samples than in the other species tested; perhaps R. rattus carries more E. coli or C. koseri , but this is something that needs to be investigated further.…”
Section: Resultssupporting
confidence: 90%
“…The results found here supports other work which suggests that markers other than the pla gene should be included to help avoid false positive results when screening for Y. pestis , as has been stressed by Janse, Hamidjaja & Reusken (2013). This was recently confirmed by Hänsch et al, as they found evidence that the pla gene is present in some strains of Escherichia coli and Citrobacter koseri (Hänsch et al, 2015). It is not clear why the homologue was present in a larger percentage of R. rattus samples than in the other species tested; perhaps R. rattus carries more E. coli or C. koseri , but this is something that needs to be investigated further.…”
Section: Resultssupporting
confidence: 90%
“…We also acknowledge that the prevalence of Y. pestis we reported may be underestimated due to limitations associated with suboptimal storage of fleas and could further be confounded by the variable number of individual fleas in diagnostic samples. Furthermore, the specificity observed for an assay targeting the pla gene must take into account homogeneity to other species (Hänsch et al 2015). In the absence of successful bacterial culture, it is recommended that alternative targets or methods confirm results utilizing a one target approach to avoid overestimation of prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The validation of ancient genomes with relatively low coverage as presented here is challenging since the DNA extracted from archaeological remains results in metagenomic data and the differentiation between target organism DNA and environmental background can be difficult. The identification of Y. pestis DNA based on PCR targeting the pla locus on the pPCP1 plasmid has theoretically been shown to be problematic (36), leading to discussions about false positive results (16). However, assignment to Y. pestis based on reads retrieved from shotgun sequencing and mapping to a reference genome also can be challenging in case of extremely low genomic coverage (3, 4).…”
Section: Discussionmentioning
confidence: 99%